PD-1 Inhibitors for Periocular Squamous Cell Carcinoma With Perineural Spread to the Orbit and Skull Base - Lu, Tracy J; Fan, Janet; Guimaraes de Sousa, Luana; Sagiv, Oded; Hernandez, Sharia; Bolanos Gomez, Lorena; Akhave, Neal; Ferrarotto, Renata; Esmaeli, Bita (Ophthalmic plastic and reconstructive surgery, 2025)
Periocular squamous cell carcinoma with perineural spread and orbital and skull base involvement is challenging to treat, as complete surgical resection is usually not feasible and radiotherapy carries a high risk of ocular toxic effects. PD-1 inhibitors have emerged as an alternative treatment for such cases. A retrospective study of all consecutive patients with periocular squamous cell carcinoma and perineural spread to the orbit treated with PD-1 inhibitors was carried out. Patients who had concurrent radiotherapy were excluded. The main outcome measure was treatment response. Most patients had recurrent squamous cell carcinoma that had been heavily treated with Mohs surgery, radiotherapy, chemotherapy, or a combination of these modalities before referral with perineural spread to the orbit and skull base. All patients had V1 involvement; other cranial nerves involved were III (n = 1), V2 (n = 1), V3 (n = 1), VI (n = 1), VII (n = 2), and VIII (n = 1). The PD-1 inhibitors cemiplimab and pembrolizumab were used in 9 patients and 1 patient, respectively. The treatment duration ranged from 2 to 24 months (median, 19 months). Six patients had a partial response, and 4 had a complete response. With a median follow-up time of 16 months, all patients were without evidence of progressive disease at last contact. Treatment with PD-1 inhibitors can lead to meaningful responses in patients with periocular squamous cell carcinoma with perineural spread to the orbit and skull base and avoids the need for radiotherapy, which is toxic to the eye. Careful long-term follow-up is needed to assess long-term response durability.